Comparing Decoupling and Driving Forces of CO2 Emissions in China and India - Jiao, Ziheng; Xing, Zhencheng; Zhang, Guofeng; Ma, Xiaolin; Wang, Haikun (Frontiers in Environmental Science, 2022)
As the two largest developing countries globally, China and India have become the top 1 and 3 carbon emitters, respectively. Quantitating their CO2 emissions in terms of the characteristics and driving factors is highly significant to mitigating global climate change. This study compiled the CO2 emission inventories from 1990 to 2017 in China and India. The Tapio model was used to analyze the decoupling between CO2 emissions and economic development, and index decomposition analysis was applied to explore the driving force behind the emissions. We found that CO2 emissions increased during 1990–2017 with an average annual growth rate of 5% in both countries. In China, the economic development has remained weakly decoupling from emissions since 2012, reaching a strong decoupling in 2017. In contrast, the contribution of India's economy to emissions continued to increase, and the decoupling status showed continuous fluctuations. Economic development and population explosion were the dominant factors driving CO2 emissions in the countries. The effect of energy intensity inhibited India’s emissions growth after 2008 with an impact degree lower than China. Our findings on the impact of the economy and emission development may provide references for other developing countries at different stages to achieve low-carbon development.